Three Kentucky Tragedies - Taylor, Richard, 1941- (Book collections on Project MUSE., 1991)
Here are three tragedies from early Kentucky history: the defeat of a small army of Kentuckians by Indians at Blue Licks in 1782, the murder of a slave by two of Thomas Jefferson's nephews in western Kentucky in 1807, and the bizarre Beauchamp-Sharp murder in Frankfort in 1825. Taylor mixes history with good storytelling and a look at how human shortcomings sometimes lead to ruin.